Turkey, the EU and the Eastern Mediterranean crisis: Militarization of foreign policy and power rivalry - Sinem Adar; Ilke Toygür (Stiftung Wissenschaft und Politik (SWP), 2020)
The Eastern Mediterranean crisis reflects two overlapping developments. On the one hand, it is a manifestation of Turkey's increasingly assertive posturing in the international arena. At the same time, it shows the intensity of the geopolitical competition between Turkey and its adversaries, such as Egypt and the UAE. The EU Member States' different levels and forms of engagement with Turkey obstruct a consensus on how to coherently respond to these developments. With accession negotiations stalled and discussions focused on areas of conflict rather than cooperation, EU-Turkey relations are mired in stalemate, while the militarization of foreign policy is becoming increasingly prevalent in the EU's southern neighbourhood.
Keywords: 320